2019
DOI: 10.1088/1741-4326/ab555f
|View full text |Cite
|
Sign up to set email alerts
|

Deep neural network Grad–Shafranov solver constrained with measured magnetic signals

Abstract: A neural network solving Grad-Shafranov equation constrained with measured magnetic signals to reconstruct magnetic equilibria in real time is developed. Database created to optimize the neural network's free parameters contain off-line EFIT results as the output of the network from 1, 118 KSTAR experimental discharges of two different campaigns. Input data to the network constitute magnetic signals measured by a Rogowski coil (plasma current), magnetic pick-up coils (normal and tangential components of magnet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 65 publications
(93 reference statements)
0
31
0
Order By: Relevance
“…These combined benefits reduce the controller development cycle and accelerate the study of alternative plasma configurations. Indeed, artificial intelligence has recently been identified as a ‘Priority Research Opportunity’ for fusion control 14 , building on demonstrated successes in reconstructing plasma-shape parameters 15 , 16 , accelerating simulations using surrogate models 17 , 18 and detecting impending plasma disruptions 19 . RL has not, however, been used for magnetic controller design, which is challenging due to high-dimensional measurements and actuation, long time horizons, rapid instability growth rates and the need to infer the plasma shape through indirect measurements.…”
Section: Mainmentioning
confidence: 99%
“…These combined benefits reduce the controller development cycle and accelerate the study of alternative plasma configurations. Indeed, artificial intelligence has recently been identified as a ‘Priority Research Opportunity’ for fusion control 14 , building on demonstrated successes in reconstructing plasma-shape parameters 15 , 16 , accelerating simulations using surrogate models 17 , 18 and detecting impending plasma disruptions 19 . RL has not, however, been used for magnetic controller design, which is challenging due to high-dimensional measurements and actuation, long time horizons, rapid instability growth rates and the need to infer the plasma shape through indirect measurements.…”
Section: Mainmentioning
confidence: 99%
“…reinforcement learning (RL) based control). In fusion research, the use of NN models to compute the plasma topology [43][44][45] and to speed up slow workflows [46][47][48][49][50] is not a novel idea, nevertheless, to our knowledge this paper represents the first which effectively addresses the 3D MHD physics in W7-X scenarios.…”
Section: Applicationmentioning
confidence: 99%
“…Similarly the reconstruction and reconstruction-control modes predict the same outputs, but use diagnostic information such as magnetic probes as inputs to the NN. Previous neural net equilibrium solvers [15][16][17][18][19][20][21][22] were developed in the spirit of reconstruction-control mode-mapping diagnostics to shaping parameters-with some exceptions such as [23] which reconstructs flux surfaces and [24] which is a fixedboundary solver. Similar to previous efforts on other machines, we obtain good predictions using the magnetic diagnostics.…”
Section: Introductionmentioning
confidence: 99%